Searching Fuzzy Information in Digital Library - Đỗ Quang Vinh (2020)
Now, method of retrieving and collecting information has changed. It's not necessary to go out for searching and accessing large available information online via portal, provided by several information providers such as: DL, digital publishers, enterprises, organizations, individuals. Accessing information is not limited by available books or magazines in the nearest library, it can be accessed via big databases and documents distributed in over the world. It's not only texts and digital data, but also includes images, sounds/voices, geographic data, video, audio, multimedia. It enables users to go a virtual travel in the museums, historic spots and wonder of natures, to participate in the concerts and virtual performance, to watch movies and read books, to listen the lectures and music - all via DL